The rise of neglected tropical diseases in the "new Texas". - Peter J Hotez (Public Library of Science (PLoS), 2018)
Within the last five years, the State of Texas has experienced either transmission or outbreaks of Ebola, chikungunya, West Nile, and Zika virus infections. Autochthonous transmission of neglected parasitic and bacterial diseases has also become increasingly reported. The rise of such emerging and neglected tropical diseases (NTDs) has not occurred by accident but instead reflects rapidly evolving changes and shifts in a "new" Texas beset by modern and globalizing forces that include rapid expansions in population together with urbanization and human migrations, altered transportation patterns, climate change, steeply declining vaccination rates, and a new paradigm of poverty known as "blue marble health." Summarized here are the major NTDs now affecting Texas. In addition to the vector-borne viral diseases highlighted above, there also is a high level of parasitic infections, including Chagas disease, trichomoniasis, and possibly leishmaniasis and toxocariasis, as well as typhus-group rickettsiosis, a vector-borne bacterial infection. I also highlight some of the key shifts in emerging and neglected disease patterns, partly due to an altered and evolving economic and ecological landscape in the new Texas, and provide some preliminary disease burden estimates for the major prevalent and incident NTDs.